Contribution of Exercise Squat Jump Split and Training Twist Bar on The Improvement of Mae Geri Chudan Kick Speed on Athlete Karate Female of DOJO WADOKAI UNIMED in 2019 - Pangondian Hotliber Purba (International Conference on Science, Education, and Technology, 2021)
The study aims to determine the contribution of the Split Squat Jump and Exercises Bar Twist to the Increasing Speed of Kick Mae Geri Chudan on Karate Female athletes at Wadokai University dojo Unimed in 2019. The research method used in the study was experimental method, the sample used in the study was 14 people. Split squat jump exercise has a significant contribution to increasing the speed of the kick Mae Geri Chudan using the right foot in the Karate Female athlete Wadokai dojo Unimed Year 2019 with a regression equation , based on the calculation results Fcount = 8.59 and Ftable ( 0.05; 1/12) = 4.75, so Farithmetic>Ftable with a contribution of 40.96%. While the kick Mae Geri Chudan using the left foot of the regression equation was and the calculation result Fcount = 5.79 and Ftable(0.05; 1/12) = 4.75, so Fcount>Ftable with a contribution of 31.36%. The exercise twist bar contributed significantly to the increase in the speed of the kick Mae Geri Chudan using the right foot in the female 's karate athlete Wadokai dojo Unimed 2019 with a regression equation , based on the calculated Fcount = 7.54 and Ftable (0.05; 1/12) = 4.75, so Farithmetic>Ftable with a contribution of 38.44%. Where as for the kick Mae Geri Chudan using the left foot the regression equation was and the calculation result Fcount = 6.89 and Ftable (0.05; 1/12) = 4.75, so Fcount>Ftablewith a contribution of 37.21%. Exercise split squat jump and twist bars together provide a significant contribution to the increase in the speed of kick Mae Geri Chudan using the right foot on a college athlete Wadokai Karate Female dojo Unimed 2019 with regression equation Based on the calculation of Farithmetic = 4.41 and Ftable (0.05; 2/11) = 3.08, so Farithmetic>Ftable with a contribution of 44%. Whereas for the kicking of Chudan game using the left foot the regression equation was and the calculation result was Fcount = 3.27 and Ftable (0.05; 2/11) = 3.08, so Fcount>Ftablewith contribution of 37%.